2012
DOI: 10.1620/tjem.227.263
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Histomorphometry in a Child with Glucocorticoid-Induced Osteoporosis

Abstract: Vertebral fractures are an under-recognized problem in children with glucocorticoid-induced osteoporosis (GIO). They cause severe back pain and spinal column deformity with a decrease of quality of life. For evaluating the bone mass, bone mineral density measurements have been widely carried out using dual energy X-ray absorptiometry. However, bone histomorphometric analyses of GIO in children are scarce. Bone histomorphometric analyses of vertebral bodies have not been reported. Our aim is to report the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…On bone biopsies and imaging studies, the above mechanisms result in unequal effects on the microarchitecture of the different types of bone [42][43][44]. It seems that the trabecular bone is principally affected, with decrease of its thickness and the development of trabecular perforations, while the cortical bone seems to be relatively spared [43][44][45]. At the same time, there is increased fat infiltration of the bone marrow which is also attributed to the excess GCS [45].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On bone biopsies and imaging studies, the above mechanisms result in unequal effects on the microarchitecture of the different types of bone [42][43][44]. It seems that the trabecular bone is principally affected, with decrease of its thickness and the development of trabecular perforations, while the cortical bone seems to be relatively spared [43][44][45]. At the same time, there is increased fat infiltration of the bone marrow which is also attributed to the excess GCS [45].…”
Section: Reviewmentioning
confidence: 99%
“…It seems that the trabecular bone is principally affected, with decrease of its thickness and the development of trabecular perforations, while the cortical bone seems to be relatively spared [43][44][45]. At the same time, there is increased fat infiltration of the bone marrow which is also attributed to the excess GCS [45]. Given the fact that the trabecular bone plays a significant role in the maintenance mechanical strength of the bone, the above alterations decrease bone quality and result in the increased risk for fractures [46].…”
Section: Reviewmentioning
confidence: 99%
“…Vertebral compression fractures, that frequently appear in osteoporosis, could be a cause for the spinal deformity [15]. The hyperkyphosis in these cases are similar to the Scheuermann kyphosis with a fixed angular kyphosis presenting an anterior wedging of the vertebra.…”
Section: Discussionmentioning
confidence: 80%
“…Vertebral fractures are an important issue in children with GC induced osteoporosis, but the BMD values may not be able to adequately reflect the increased risk of fractures. The alteration in bone microstructure must be considered when assessing the risk of fracture and can be measured with TBS, that can be extracted from DXA images of the lumbar spine [14,15]. A low bone density or deterioration to the bone microstructure of the vertebrae and possible vertebral fracture can lead to deformities of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…3 Compared with long-term use of GCs, the role of short-term use of GCs on the skeleton is more complex and at time considered paradoxical. [4][5][6] Ogoshi et al 7 have reported that the whole body bone mineral density (BMD) and bone formation rate increased in 3-month-old rats treated with GC for 4 weeks. However, some experimental evidences have indicated that GCs excess induce an initial but transient loss of BMD because of an early up-regulation of bone resorption.…”
Section: Introductionmentioning
confidence: 99%